Pengaruh Work Life Balance dan Pengembangan Karir terhadap Produktivitas Kerja Karyawan di Kantor Dinas Pariwisata Kota Makassar - St Khumairah; Romansyah Sahabuddin; Uhud Dermawan Natsir; Muh. Ichwan Musa; Burhanuddin Burhanuddin (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of work-life balance and career development on the work productivity of employees at the Makassar City Tourism Office.The research uses a quantitative approach with a sample of 55 permanent employees. Data were collected through observation, questionnaires, and documentation, and then analyzed using multiple linear regression with the help of IBM SPSS 26.0. The results of the study show that work-life balance partially has a positive and significant effect on work productivity. This is evidenced by the significance value of 0.000 < 0.05 and t-count 3.840 > t-table 2.007. Career development also had a positive and significant influence with a significance value of 0.000 < 0.05 and t-count 9,750 > t-table 2,007. Simultaneously, work-life balance and career development have a significant influence on work productivity. In conclusion, work-life balance and career development are important factors in increasing employee productivity. This shows the need for organizations to pay attention to employee work-life balance and good career management to achieve optimal performance.